Diminished Return of Employment on Ever Smoking Among Hispanic Whites in Los Angeles - Shervin Assari; Ritesh Mistry (Mary Ann Liebert, 2019)
Purpose: According to the Minorities' Diminished Return (MDR) theory, socioeconomic status (SES) indicators such as employment status produce smaller tangible outcomes for racial and ethnic minority groups, however, very limited information exists on such diminished returns for Hispanics. To test whether MDR also holds for the social patterning of smoking behaviors among white adults, this study explored ethnic differences in the association between employment status and ever smoking in a representative sample of adults in Los Angeles. Methods: Los Angeles Family and Neighborhood Survey 2001 included 907 non-Hispanic white and 2117 Hispanic white adults (ages 18 or older). Ethnicity, gender, age, employment status, marital status, immigration status, and ever smoking were measured. Logistic regression models were used for data analysis. Results: In the pooled sample that included both non-Hispanic whites and Hispanic whites, being employed was associated with lower odds of ever smoking, net of covariates. A significant interaction was found between ethnicity and employment status on odds of ever smoking, suggesting a stronger inverse association between employment status and ever smoking for non-Hispanic whites than Hispanic whites. Ethnic specific models showed an inverse association between being employed and ever smoking status for non-Hispanic whites, but not for Hispanic whites. Conclusion: Even among whites, whether or not employment reduces the risk of ever smoking may depend on ethnicity, with Hispanics being at a disadvantage relative to non-Hispanic whites in terms of lower odds of ever smoking from their employment status.